The Influence of Experimental Marketing on Purchasing Decision: The Mediating Role of Brand Identity - Sitepu, Rimenda Aminarosa; Wahjudono, Denny Bernardus Kurnia; Tambunan, Damelina Basauli; Kodrat, David Sukardi; Harianto, Eric (Migration Letters, 2024)
This study explores the impact of two primary factors, namely experimental marketing and brand identity, on purchasing decisions within micro, small, and medium enterprises (MSMEs). The main aim of this investigation is to assess how experimental marketing and brand identity affect purchasing decisions, with a specific focus on how brand identity moderates the relationship between experimental marketing and purchasing decisions. Employing partial least squares structural equation modeling (PLS-SEM), the study analyzes data collected from 633 research subjects who are consumers of the brand mixue. The findings reveal that experimental marketing significantly and positively influences purchasing decisions, while resources also have a notable positive impact on purchasing decisions. Moreover, experimental marketing significantly impacts brand identity. Of particular interest is the discovery that brand identity can bolster the positive association between experimental marketing and purchasing decisions. These findings contribute substantially to our comprehension of the intricate factors shaping purchasing decisions in the Indonesian MSME context, particularly through the interaction between experimental marketing and brand identity. Consequently, the implications of this research can serve as a foundation for future marketing strategies that are both more effective and contextually appropriate.